(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: تعتبر الجماعات المحلية والمتمثلة في البلدية والولاية تكريسا للامركزية الإدارية في الجزائر، تتمتعان بالشخصية المعنوية والاستقلالية المالية، تمارسان التكفل بحاجات المواطنين في الإقليم من خلال هيئة تداولية وأخرى تنفيذية، ولما كان الأصل في نظام اللامركزية توزيع الوظيفة الإدارية بين السلطة المركزية وهذه الهيئات، تم إرساء ترسانة قانونية لضمان السير الحسن لهذه الهيئات من خلال ما يعرف بالرقابة الإدارية ضمانا للمشروعية التي تحقق وحدة الدولة وتحفظها من التفكك، وهذا ما سنبينه من خلال قانون البلدية11/10، وقانون الولاية12/07. كلمات دالة :الوصاية الإدارية، الرقابة،الوالي، المجالس المنتخبة Abstract: The local communities represented by the municipality and the State are considered as consecration of administrative decentralization in Algeria. They enjoy moral personality and financial autonomy. They exercise care for the needs of citizens in the region through a deliberative and executive body, and since the principle in the decentralized system is the distribution of the administrative function between the central authority and these bodies, a legal arsenal was established to ensure the good functioning of these bodies through what is known as administrative control, To ensure the legitimacy that achieves the unity of the state and preserves it from disintegration, and this is what we will find out from the Municipal Law 10/11, and the State Law 07/12.Key words: Administrative control; supervision; the governor; elected councils